Comparison of UAV Drone and Online Terrain Model for Railway Route Planning - Wahyu Tamtomo Adi; Adya aghastya; Nanda Ahda Imron; Nurul Fitria Apriliani; Izza Anwer; Porntep Puangprakhon (Politeknik Perkeretaapian Indonesia Madiun, 2022)
This research tried to compare Digital Elevation Model (DEM) results from UAV Drone Survey with online DEM with a study case a railway route planning from Semarang to Demak in Central Jawa. The terrain model was resulted by Agisoft Metashape software and was compared to DEM from GoogleEarth, BING, SRTM, ASTERGDEM and DEMNAS by using Global Mapper sofware. The comparison was conducted by generating contour drawing for each model, along with graphical and statistical analysis. The results shown that the DEM Model from UAV Drone Survey result can meet the standard accurcy needed. The result of comparison from other the online DEM resulted that DEMNAS and ASTER GDEM have the stronges correlation among other DEM resources. The finding suggested for a carefull consideration to use open source DEM Data for perelyminary design odr Detail Engineering Design, especially for railway infrastructure project.